KANDUNGAN TOTAL FENOL DALAM EKSTRAK METANOL DAN ETIL ASETAT Caulerpa racemosa (TOTAL PHENOL CONTENTS IN METHANOL AND ETHYL ACETATE EXTRACTS OF Caulerpa racemosa) - ilmauwati Qurniasih; Ikha Safitri; Anthoni B. Aritonang; Warsidah Warsidah; Shifa Helena (Indonesian Journal of Pure and Applied Chemistry, 2022)
Caulerpa racemosa belongs to Chlorophyceae grow abundantly along Indonesian waters, including Kabung Island, West Kalimantan. This species has important role and is able to synthesize a wide range of bioactive compounds that are potential to be developed. However, their existence have not been used optimally. This study aims to determine the bioactive compound and evaluate total phenol contents in methanol and ethyl acetate of C. racemosa from Kabung Island. The methods in this study were maceration, phytochemicals, and Folin-Ciocalteau using Atomic Absorption Spectroscopy (AAS). The result showed that methanol and ethyl acetate extracts of C. racemosa contained alkaloids, flavonoids, saponins, phenols, and tannins. Thus, the total phenol content in ethyl acetate extracts was 0.077817 mgGAE/g while in methanol extract was 0.05682 mgGAE/g, respectively. This value was classified as low category.